Clinical and radiological presentation of pleomorphic lobular carcinoma in-situ and its association with invasive malignancy. (2015) - Kirwan, Cliona C.; Jain, Yogesh; Morris, Kit; Howe, Miles; Harvey, James R.
Abstract: Aims: Optimal management of Pleomorphic lobular carcinoma-in-situ (PLCIS) remains a matter of debate. We aimed to identify presenting clinical, radiological and histopathological features and oncological outcome of PLCIS. Methods: From a prospectively maintained histopathology database between January 2000 and June 2014, all patients with a diagnosis of PLCIS were identified, and retrospective review of case notes performed. Results: Of 19 cases, only 3 presented as symptomatic lumps, however 11 had mass lesions on imaging. All patients underwent definitive cancer surgery with wide margins. In all but three cases, PLCIS was associated with additional pathologies (DCIS, ILC, IDC), highlighting the pluripotential development of breast cancer. Of the six cases with no invasion, three were oestrogen receptor negative. There were no local or systemic recurrences over the median follow up period of 66 months. Conclusion: PLCIS presenting without invasion is rare and, unlike invasive cancer and ductal carcinoma-in-situ, does not appear to be predominantly associated with ER positivity. However, PLCIS is almost universally associated with invasive cancer or DCIS, and should be managed with wide excision and clear margins. Clinical practise points: ● There is uncertainty surrounding the management of PLCIS as highlighted by the lack of guidelines on this unusual disease entity. ● The commonest presentation of PLCIS is in asymptomatic women through breast screening. ● PLCIS presenting without invasion is rare and unlike invasive breast cancer and DCIS, does not appear to be predominantly commonly associated with ER positivity. ● PLCIS is commonly associated with in-situ and invasive lesions, with 58% of cases associated with invasive lobular carcinoma in this current series. ● Breast conserving surgery with clear margins and adjuvant treatment as dictated by associated pathology and molecular profile is recommended for PLCIS. ● In patients presenting with a mass lesion, and pure PLCIS on diagnostic core biopsy: A re-biopsy, ideally using vacuum-assistance is recommended, to attempt to upgrade the tumour pre-operatively, as invasion is almost universal in this subset. The common association of PLCIS with the presence of invasive ductal carcinoma, invasive lobular carcinoma, ductal carcinoma in-situ and lobular carcinoma-in-situ suggests a single pluripotent stem cell origin for these cancer subtypes.